Cross countries: International comparisons of intergenerational trends - Fahmida Rahman; Daniel Tomlinson (Luxembourg Income Study (LIS), 2018)
This report explores the extent to which the UK's generational living standards challenge is replicated in other high-income economies, focusing on trends in household income and experiences in the labour and housing markets. We look at the shared backdrop to these trends across advanced economies: demography - the fiscal challenges posed by falling birth rates and rising dependency ratios - and the financial crisis - sharp falls in real GDP per capita across almost all advanced economies in the late 2000s (Section 1), before examining gains (and losses) in real household income growth between generations of adults that are still alive today i.e. generations born between 1911 and 2000 (Section 2). We then focus on post-crisis trends in pay and employment in advanced economies as well as some of the long-run, more structural, challenges facing young people in labour markets (Section 3). We finish by examining the impact that changes in home ownership rates and housing costs have had on the prospects for young people here in the UK and in other places in which housing has been identified as a clear issue for young people (Section 4).
Keywords: 330